2016
DOI: 10.1177/1756283x16645501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of dual red imaging in colorectal endoscopic submucosal dissection: a pilot study

Abstract: Background: Dual red imaging (DRI), a novel image-enhanced endoscopic technique, is expected to improve visibility of thin vessels, but no reports of the clinical use of DRI in colorectal endoscopic submucosal dissection (ESD) have been published. We aimed to compare the visibility of vessels, demarcation line between the submucosal and muscle layers after injection of hyaluronate sodium with minute indigo carmine, and fibrosis on DRI with that on white light imaging (WLI). We applied the principle of DRI to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…We previously reported that DRI improved the visibility of arteries and the submucosal layer in colorectal ESD. 6 Because DRI makes hemostasis easier in many cases, DRI greatly improves the visibility of blood vessels. 6,14 The orange color of the bloodstream makes it easy to assess the bleeding point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that DRI improved the visibility of arteries and the submucosal layer in colorectal ESD. 6 Because DRI makes hemostasis easier in many cases, DRI greatly improves the visibility of blood vessels. 6,14 The orange color of the bloodstream makes it easy to assess the bleeding point.…”
Section: Discussionmentioning
confidence: 99%
“…They scored the images from DRI relative to the corresponding images from WLI for visibility of blood vessels according to the following scale: +2 (improved visibility), +1 (slightly improved visibility), 0 (visibility equivalent to that of WLI), -1 (worsened visibility), and -2 (visibility lost) ( Table 1). 6,7 The total scores of the 5 endoscopists were calculated. In this study, the highest possible score was +10 and the lowest was -10.…”
Section: Evaluation In Videosmentioning
confidence: 99%
See 1 more Smart Citation
“…Naganuma et al [2] reported that DRI was useful to assess the severity of inflammation using the deep vascular pattern in patients with ulcerative colitis. Ninomiya et al [3] proposed that DRI may enhance both the safety and speed of colorectal endoscopic submucosal dissection by improving the visibility of the arteries. Furuichi et al [4] similarly found that DRI increased the visibility of the esophageal varices and red color sign.…”
Section: Discussionmentioning
confidence: 99%
“…The displayed image shows that the 600 nm light is significantly more attenuated than the 630 nm light, which enhances the visibility of the deep vessels. 5 When blood vessels are absent, the reflected light is visualized with low attenuation; however, the reflected 600 nm light becomes highly attenuated in the presence of highly concentrated blood when compared to the presence of low-concentrated blood. Thus, the reflected image becomes reddish with the concomitant occurrence of a color contrast.…”
mentioning
confidence: 99%